2008
DOI: 10.2169/internalmedicine.47.1080
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoaldosteronism Caused by Combined Administration of Cilostazol and Glycyrrhizin

Abstract: We report a case of obvious pseudoaldosteronism which occurred after the additional administration of cilostazol against arteriosclerosis obliterans (ASO)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…These results suggest that SK is an effective herbal medicine for not only spontaneous contractions but also oxytocin‐ and PGF 2α ‐induced contractions in clinical critical situations and that the effect of SK on smooth muscle contractions is due to K. SK may decrease the risk of premature delivery caused by premature uterine contractions. However, it is necessary to use SK with caution because there are some reports that it increases the risk of pseudoaldosteronism with hypokalemia, hypertension, sodium and body fluid retention edema, and weight gain 18–21 . Further studies are needed before SK can be utilized for prevention of premature delivery.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that SK is an effective herbal medicine for not only spontaneous contractions but also oxytocin‐ and PGF 2α ‐induced contractions in clinical critical situations and that the effect of SK on smooth muscle contractions is due to K. SK may decrease the risk of premature delivery caused by premature uterine contractions. However, it is necessary to use SK with caution because there are some reports that it increases the risk of pseudoaldosteronism with hypokalemia, hypertension, sodium and body fluid retention edema, and weight gain 18–21 . Further studies are needed before SK can be utilized for prevention of premature delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The adverse reactions of MTX include nausea, vomiting, diarrhea, and hepatotoxicity [87,88]. A case report showed that combined administration of GA and cilostazol caused pseudoaldosteronism [89]. Therefore, the concurrent use of GA with MTX or cilostazol is not recommended.…”
Section: Inductive Effect Of Liver Enzymementioning
confidence: 99%
“…Pseudoaldosteronism is a well-known adverse reaction in patients receiving licorice and its more purified product, glycyrrhizic acid (GA) (15). A daily intake of 10 mg/day or 0.2 mg/kg/day of GA is considered safe for most healthy adults, using a safety factor of 10 (16,17).…”
Section: Discussionmentioning
confidence: 99%